D1- and D2-type dopamine receptors are immunolocalized in pial and layer I astrocytes in the rat cerebral cortex - Oda, Satoko; Funato, Hiromasa (Frontiers in Neuroanatomy, 2023)
Pial astrocytes, a cellular component of the cerebral cortex surface structure, are observed in a wide range of mammalian species. Despite being recognized as such, the functional potential of pial astrocytes has long been overlooked. Our previous research demonstrated that pial astrocytes exhibit stronger immunoreactivity for muscarinic acetylcholine receptor M1 than protoplasmic astrocytes, indicating sensitivity to neuromodulators. Here, we examined whether pial astrocytes express receptors for dopamine, another crucial neuromodulator of cortical activity. We investigated the immunolocalization of each dopamine receptor subtype (D1R, D2R, D4R, D5R) in the rat cerebral cortex, and compared the intensity of immunoreactivity between pial astrocytes, protoplasmic astrocytes, and pyramidal cells. Our findings revealed that pial astrocytes and layer I astrocytes exhibit stronger D1R- and D4R-immunoreactivity than D2R and D5R. These immunoreactivities were primarily localized in the somata and thick processes of pial and layer I astrocytes. In contrast, protoplasmic astrocytes located in cortical layers II -VI displayed low or negligible immunoreactivities for dopamine receptors. D4R- and D5R-immunopositivity was distributed throughout pyramidal cells including somata and apical dendrites. These findings suggest that the dopaminergic system may regulate the activity of pial and layer I astrocytes via D1R and D4R.